Empowering internet of things (IoT) through big data - Sutjiatmo B.P.; Erwinsyah A.; Laxmi Lydia E.; Shankar K.; Nguyen P.T.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The coming of new advancements, devices and union of remote correspondence, computerized hardware, and miniaturized scale electro-mechanical frameworks (MEMS) advances have brought about the development of Internet of Things (IoT) which thusly delivers an enormous measure of information. IoT helps in diminishing expenses and expanding income, however at the expense of creating tremendous information. The organization of colossal data in an always stretching out framework offers rise to non-irrelevant worries as for data gathering capability, data planning, assessment, and security. This paper describe the benefits of big data in IOT. And also describe architecture and various applications of IOT. BEIESP.